1456. Resistance Mechanisms of Tigecycline in Enterococcus faecalis. (31st December 2020) - Bai, Bing; Wen, Zewen; Lin, Zhiwei; H, Tam Vincent; Yu, Zhijian
Abstract: Background: Enterococcus faecalis have been regarded as one of the leading causes of the nosocomial infections worldwide. Tigecycline (TGC) is considered as a choice of last resort for the treatment of infections caused by multidrug-resistant E. faecalis, however, the emergence of TGC non-susceptibility has posted the therapeutic challenge. Non-susceptibility in clinical strains could be due to resistance (MIC >0.5 mg/l) or heteroresistance. Therefore, this study aimed to understand the underlying molecular mechanisms of TGC resistance and heteroresistance in E. faecalis . Methods: In vitro induction experiments were carried out under TGC pressure with two TGC- sensitive E. faecalis strains. Heteroresistance was evaluated by population analysis profiling (PAP) in 270 clinical TGC- sensitive E. faecalis strains. TGC susceptibility was determined by the agar dilution method. Resistance and heteroresistance mechanisms were investigated by identifying genetic mutations in tetracycline (Tet) target sites and susceptibility testing in the presence of the efflux protein inhibitors phenylalanine-arginine-β-naphthylamide (PaβN) and carbonyl cyanide m chlorophenylhydrazine (CCCP). Comparison of single nucleotide polymorphism in the whole genome between the parental isolate and two TGC-resistant strains were investigated by next-generation sequencing. Results: No mutations in Tet target sites in seven TGC heteroresistant strains were present, whereas the mutations in Tet target sites of seven TGC-resistant E. faecalis were frequently found (Table 1). TGC MICs in heteroresistant strains were reduced by CCCP (Table 2). Whole genome sequencing revealed the same non-synonymous mutations and transcoding deletions in the exons of several genes encoding for various enzymes or transfer systems (Table 3). Table 1. The characteristics of the antimicrobial susceptibility, resistance mechanism of TGC-induced resistant isolates Table 2. Characteristics of clinical heteroresistant mother E. faecalis strains and heteroresistance-derived E. faecalis clones Table 3. List of mutation-related genes, amino acids and proteins by comparison of whole genome between the parental isolate and the TGC-induced resistant strains Conclusion: Our data indicated that the main mechanism of TGC heteroresistance in E. faecalis might be associated with the efflux pumps. TGC resistance in E. faecalis was associated with mutations in the 16SrRNA site or 30S ribosome protein S10. The genetic mutations in several enzymes and transfer systems might also participate in the resistance development to TGC in E. faecalis . Disclosures: All Authors : No reported disclosures